ANALISIS KESUKSESAN PENERAPAN SISTEM INFORMASI E-SPT PAJAK PENJUALAN (PPN) TERHADAP KEPATUHAN PAJAK PADA KANTOR PELAYANAN PAJAK MADYA A DAN KANTOR PELAYANAN PAJAK MADYA B - Etik Ipda Riyani (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2017)
Etik Ipda Riyani: This study aimed to analyze the relationship between the success of the implementation of the information system e-SPT Sales Tax (e-SPT PPN) to tax compliance. The model used in the study was the model of success of information systems updated D & M IS Success Model. This model is based on six measures of success is the quality information system (System Quality), the quality of information (Information Quality), quality of service (Service Quality), user interest (Intention to Use), the satisfaction of users (User Satisfaction), and tax compliance. The population of this research is all taxpayer is incorporated and registered in Madya Tax Office A and B. Researchers using simple random sampling in the sampling. The analytical tool used in this study were Path Analysis (Path Analysis).The results showed the successful implementation of the information system e-SPT PPN with dimensions System Quality, Information Quality, and Service Quality, Intention to Use and User Satisfaction effect on Tax Compliance.Key words: the success of information systems, e-SPT VAT, tax compliance